2006
DOI: 10.1021/jp062607t
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and 2D NMR Studies on Hydrogen-Bonding Aggregates of Cholesterol in Low-Polarity Organic Solvents

Abstract: Self-diffusion coefficients (D) are measured for normal (nondeuterated) and deuterated cholesterol-d(6) (C26 and C27 methyl groups deuterated) in 1-octanol, chloroform, and cyclohexane at concentrations of 1-700 mM by varying the impurity water concentration (>2 mM) and temperature (30-50 degrees C). The pulsed field gradient spin-echo (PGSE) (1)H and (2)H NMR were used, respectively, at 600 and 92 MHz. At 30 degrees C, the hydrodynamic radius (R) obtained at 20 mM from the D value and solvent viscosity is 5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…This suggests formation of cholesterol aggregates, in agreement with reports in the literature. [69][70][71][72][73][74] In contrast, the particle size does not change for cholesterol in 1-octanol as a function of concentration, consistent with the interpretation that cholesterol disperses as monomers in 1-octanol. 70 With cholesterol's solution behavior in both cyclohexane and 1-octanol as reference points, we investigated the mixed AOT reverse micelle/cholesterol system.…”
Section: Resultssupporting
confidence: 66%
“…This suggests formation of cholesterol aggregates, in agreement with reports in the literature. [69][70][71][72][73][74] In contrast, the particle size does not change for cholesterol in 1-octanol as a function of concentration, consistent with the interpretation that cholesterol disperses as monomers in 1-octanol. 70 With cholesterol's solution behavior in both cyclohexane and 1-octanol as reference points, we investigated the mixed AOT reverse micelle/cholesterol system.…”
Section: Resultssupporting
confidence: 66%
“…Another interesting example of solvent effect on the extent of aggregation has been reported by Nakahara and co-workers studying cholesterol in low-polarity organic solvents that mimic the membrane bilayer hydrophobic core. 24 They found that cholesterol forms aggregates in chloroform and cyclohexane but it does not in 1-octanol. The aggregation process is driven by the hydrogen bonding.…”
Section: Changing Solventmentioning
confidence: 99%
“…Ion Pairing and Salt Structure in Organic Salts first example of the use of 195 Pt relaxation characteristics for this purpose. [36] X-ray study of 6 c: Relative to the CF 3 SO 3 À anion, the CH 3 SO 3 À anion is not frequently used. Consequently we have determined the solid-state structure of salt 6 c and show this in Figure 14a along with selected bond lengths and bond angles.…”
Section: Full Papermentioning
confidence: 99%